2022
DOI: 10.1111/cpr.13213
|View full text |Cite
|
Sign up to set email alerts
|

In situ analysis of acupuncture protecting dopaminergic neurons from lipid peroxidative damage in mice of Parkinson's disease

Abstract: Objectives Acupuncture stimulation has proven to protect dopaminergic neurons from oxidative damage in animal models of Parkinson's disease (PD), but it remains unclear about the in situ information of biochemical components in dopaminergic neurons. Here, we aimed to analyse in situ changes of biochemical components and lipid peroxidation levels in dopaminergic neurons in PD mice treated with acupuncture by synchrotron FTIR micro‐spectroscopy technique. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…As there were some differences in the baseline between the two studies, more quantitative studies with better homogeneity will be needed to confirm this conclusion. Animal experiments have proved that there is a certain scientific basis for acupuncture to improve motor function in PD, such as reducing neuronal apoptosis of the striatum (Lu et al, 2012 ), normalizing the brain functional connectivity (Oh et al, 2022 ), inhibiting the level of lipid peroxides in dopaminergic neurons and protect neurons from oxidative damage (Zuo et al, 2022 ). However, to the best of our knowledge, there are no multi-session animal experiments to explore the dose-response mechanism of acupuncture in the treatment of PD, so high-quality scientific evidence is still needed.…”
Section: Discussionmentioning
confidence: 99%
“…As there were some differences in the baseline between the two studies, more quantitative studies with better homogeneity will be needed to confirm this conclusion. Animal experiments have proved that there is a certain scientific basis for acupuncture to improve motor function in PD, such as reducing neuronal apoptosis of the striatum (Lu et al, 2012 ), normalizing the brain functional connectivity (Oh et al, 2022 ), inhibiting the level of lipid peroxides in dopaminergic neurons and protect neurons from oxidative damage (Zuo et al, 2022 ). However, to the best of our knowledge, there are no multi-session animal experiments to explore the dose-response mechanism of acupuncture in the treatment of PD, so high-quality scientific evidence is still needed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its widespread use, international acknowledgment of acupuncture's e cacy in PD remains limited, primarily due to the predominant publication of evidence-based literature in Chinese journals, often characterized by varying quantity and quality. Numerous animal studies underscore acupuncture's potential in mitigating PD-associated neuronal apoptosis in the striatum (54), normalizing brain functional connectivity(36), and reducing lipid peroxide levels in dopaminergic neurons, thereby protecting against oxidative damage (37).…”
Section: The Mechanism Of Acupuncture On Pd and Microbiome Dysbiosismentioning
confidence: 99%
“…Available evidence suggests that acupuncture treatment has the potential to alleviate motor and NMS of PD, but the underlying mechanisms are unclear ( 27 29 ). The neuroprotective effects of acupuncture on neurodegenerative lesions in animal models of PD are mainly focused on cerebral neurons ( 30 32 ), and no studies have yet reported the effects of acupuncture on the ENS. Here, we investigate the mechanisms of acupuncture to alleviate bowel dysfunction in PD constipation by revealing the effects of acupuncture treatment on the ENS myenteric nervous plexus and its neurotransmitters in an animal model of PD.…”
Section: Introductionmentioning
confidence: 99%